Comprehensive Operative Note Templates for Primary and Revision Total Hip and Knee Arthroplasty - Electricwala, Ali J. (Open Orthop J, 2016)
BACKGROUND: Adequate preoperative planning is the first and most crucial step in the successful completion of a revision total joint arthroplasty. The purpose of this study was to evaluate the availability, adequacy and accuracy of operative notes of primary surgeries in patients requiring subsequent revision and to construct comprehensive templates of minimum necessary information required in the operative notes to further simplify re-operations, if they should become necessary. METHODS: The operative notes of 144 patients (80 revision THA’s and 64 revision TKA’s) who underwent revision total joint arthroplasty at Stanford Hospital and Clinics in the year 2013 were reviewed. We assessed the availability of operative notes and implant stickers prior to revision total joint arthroplasty. The availability of implant details within the operative notes was assessed against the available surgical stickers for adequacy and accuracy. Statistical comparisons were made using the Fischer-exact test and a P-value of less than 0.05 was considered statistically significant. RESULTS: The primary operative note was available in 68 of 144 revisions (47%), 39 of 80 revision THAs (49%) and 29 of 66 revision TKAs (44%, p = 0.619). Primary implant stickers were available in 46 of 144 revisions (32%), 26 of 80 revision THAs (32%) and 20 of 66 revision TKAs (30%, p = 0.859). Utilizing the operative notes and implant stickers combined identified accurate primary implant details in only 40 of the 80 revision THAs (50%) and 34 of all 66 revision TKAs (52%, p = 0.870). CONCLUSION: Operative notes are often unavailable or fail to provide the necessary information required which makes planning and execution of revision hip and knee athroplasty difficult. This emphasizes the need for enhancing the quality of operative notes and records of patient information. Based on this information, we provide comprehensive operative note templates for primary and revision total hip and knee arthroplasty.